Data governance reference model under the lean methodology for the implementation of successful initiatives in the Peruvian microfinance sector - Romero, Alvaro (2019)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.